Prospects and Threats of Groundwater Development for Town Water Supply and Irrigation Development in Rift Valley Plains - E, Assefa; A, Tenalem; A, Tilahun (International Journal of Hydrology Research, 2022)
This work presents prospects and threats of groundwater development for town water supply and irrigation development in rift valley plains. The Becho alluvial plain gets recharge from rainfall, floods from dendritic stream networks and groundwater transfers from adjacent basins. Recharge estimation from two base flow separation methods indicated that the plain is getting an annual recharge of 89.8 mm. There are cyclic rain shortages every three to four years. The poor rainfall seasons record nearly half of the best rainfall seasons. Abstraction and water levels in Becho plain are in the region of 25,000 m3/day and 10 meters, respectively. But these are each less than ten folds of that in the adjacent Akaki basin. Steady and transient state groundwater flow modelling of a basin hosting the Becho and Akaki catchments showed that the former is nearly in steady state while the latter is under excessive mining. Time series of well water level measurements, base flow separation and transient groundwater flow modeling suggest that the Becho plain has potential for motorized irrigation and ground water development under regulated situations. However, in the face of lower transmissivity and storage coefficients, utmost care is needed to minimize propagation of groundwater level decline from adjacent Akaki wellfield.